Şükrî: Hz. Ali İle Kahkaha Sultan Cengi - Kavlak, Tuğba (My University, 2018)
Bu çalışmada Süleymaniye Kütüphanesi Denizli Bölümü’nde 377 numarayla kayıtlı Şükrî ve cenknâme türündeki eseri konu edinilmiştir. Eserde Hz. Ali’nin cenklerini anlatan şiirlere yer verilmiştir. Şiirler alfabetik sıraya göre düzenlenmiş olup ağırlıklı olarak Türkçe kelimeler kullanılmıştır. Şükrî mahlasına sahip pekçok şair olması ve tezkirelerde de Şükrî hakkında bilgi bulunmaması şairin tespitini zorlaştırmıştır. Şiirlerinden hareketle edebî kişiliği değerlendirilmiştir.Eser üç bölümde incelenmiştir. Birinci bölümde Şükrî’nin hayatı ve edebî kişiliğine değinilmiş; ikinci bölümde eser, şekil ve içerik açısından incelenmiştir. Üçüncü bölümde ise eserin transkripsiyonlu metni verilmiştir. Bu çalışmayla Şükrî ve şiirleri tanıtılarak, Türk edebiyatına katkı sağlanması amaçlanmıştır.

This study is about a work named Şükrî and work in cenknâme which is registered to Süleymaniye Library Denizli Deparment with 377 Library of Congress Control Number(LCCN). In this work, poems that tell about Hz. Ali's battles are mentioned. Poems are listed in alphabetical order. In addition to this, Turkish words have been mainly used. It is very hard to determine the poet's identity because of that there are many poets who has been called by Şükrî's nickname and also there isn't enough information about Şükrî in the collection of biographies. In this study, his literary identity is demonstrated based on his poems.This work will be examined in 3 sections. The first section is about Şükrî's biography and his literary personality. When you start the second section, Divan is examined in terms of structure and content. The text of work is given with transcription in the 3 section. This study aims to introduce Şükrî and his poems. At the same time, the main purpose is making a contribution to Turkish Literature.
Keywords: Classical Turkish Literature; Destanlar; Efsaneler; Hz. Ali cenkleri; Hz. Ali, Halife, (600-661); Hz. Ali's battles; Kan Kalesi; Klasik Türk Edebiyatı; Şükrî; Tarih; The Castle of Blood; Türk dili ve edebiyatı